End of economics - Perelman, Michael (London, 1996)
Most economic theory assumes a pure capitalism of perfect competition. Even when perfect competition does not exist, many politicians and captains of industry pay a great deal of lip service to the idea of the market, while doing all they can to protect business from market forces. This book goes beyond this rhetoric to explore how, even in the United States - the most capitalist of all countries the market has always been subjected to numerous constraints. Further, in the opinion of many figures from the right, these ameliorating factors have been a very good thing. As well as discussing the opinions of economists, the book looks at the opinions and practices of such figures as Henry Ford, J. P. Morgan, and Herbert Hoover.
Keywords: Economics - History - 20th century